Vendetta: A Story of One Forgotten - Corelli, Marie, 1855-1924 (Salt Lake City, UT : Project Gutenberg, 2003)
"Vendetta: A Story of One Forgotten" by Marie Corelli is a romance novel published in 1886. After being mistakenly declared dead during a cholera outbreak, Italian Count Fabio Romani escapes his tomb and discovers his wife and best friend have been conducting an affair. Adopting a new identity as wealthy bachelor Cesare Oliva, the count orchestrates an elaborate scheme of revenge against those who betrayed him. Corelli's second novel became a popular success despite receiving mixed critical reviews. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Vendetta!
Release date is 2003-08-01
Charles Franks and the Online Distributed Proofreading Team. HTML version by Al Haines
Keywords: Adultery -- Fiction; Revenge -- Fiction; Italy -- Fiction; Vendetta -- Fiction